The Translation and Dubbing of 'Fuck' into Catalan: The Case of From Dusk till Dawn - Dídac Pujol (JoSTrans: The Journal of Specialised Translation)
The word 'fuck' is the vulgar word par excellence in English, and its translation into Catalan has been little studied.1 At a local level, this paper aims to be the first systematic analysis of the translation for dubbing of 'fuck' and its compounds (e.g. 'motherfuck') and derivatives (e.g. 'fucking') into Catalan, especially as practised by the Catalan national television, Televisió de Catalunya. On a more global level, it is hoped that the present study becomes a useful frame of reference for translation scholars and future translators of one of the coarsest and most transgressive words in the English language. The corpus employed is the 1996 film From Dusk till Dawn / Obert fins a la matinada, directed by Robert Rodriguez with a script by Quentin Tarantino. The paper takes into account five dimensions: lexical, contextual, pragmatic, cultural and characterisational.